Tara agribusiness system of Peru: performance and commercial dynamics (Agroindustrial Science, 2022)
The objective of the research was to evaluate the performance of tara agribusiness system-ABS of Peru according to the commercial dynamics of the international market. The methodology of Diagnosis and Strategic Management of an Agribusiness System was used and as tools the analysis of market dynamics and discrete structural analysis for the ABS, based on the review of bibliographic sources and the application of semi-structured interviews. The ABS presents a growth in exports of tara derivatives based on demand. Powdered tara and tara mucilages are the main export products, however, market disruptions fluctuate their sales prices. In this context, the ABS has an institutional environment that encourages the production of tara and derivatives for the international market, however, a limited performance of small producers is evident due to their high informality, low scale, weak collective level and low technological level for the production of tara. Therefore, the commercial dynamics of the ABS is limited by the low performance of the producers.
Keywords: Caesalpinia spinosa; agribusiness; export; producers; limitations